Final report on assessment instruments for a prospective payment system - Buchanan, Joan, 1947- (Rand Health, 2004)
A design for a prospective payment system (PPS) for inpatient rehabilitation facilities that pay providers a predetermined, fixed price (per day, per episode, or per case). Since the payment is independent of the amount of service provided, these systems are thought to create an incentive for efficient, cost-conscious care. A new assessment tool has been developed for PPS for rehabilitation facilities and this study provides an evaluation of it.